Artificial Intelligence and Machine Learning in Waste Management and Recycling - Ahmed, Alim Al Ayub; Asadullah, ABM (Engineering International, 2020)
Waste management is one of the biggest problems facing the world in any developed or developing country. An important aspect of waste management is that the waste bin in the open space is properly filled before the next cleaning process begins. This can eventually lead to various hazards such as dirt and bad odor in the area, which can lead to the spread of various diseases. Population growth has significantly reduced toilets through the waste management system. Laying garbage in public places creates a polluted environment. To eliminate or reduce waste and maintain good hygiene, it requires a waste-based waste management system. The need for proper waste management is not limited to proper collection and disposal of waste. It continues to be a waste disposal and recyclable level. Recycling is considered a major benefit because in addition to waste disposal, our reliance on immature materials is declining. By recycling metal, plastic and glass, the use of decomposing waste can extend beyond compost and manure. Metals can be reused and plastic can be mixed with clay filler, which can lead to soil compaction. After deep cleaning the glass construction material can be broken down and re-melted into new articles. This article is about machine learning and the use of artificial intelligence in the most viable areas and understanding the full need for human communication.